Association between Maternal Age and Awarnes of Pregnancy Danger Sign among Pregnant Women : (At the Tapa Health Center, Bone Bolango Regency) - Jumratul Aini; Nila Widya Keswara; Rosyidah Alfitri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Various factors influence pregnant women's knowledge of pregnancy danger signs, including age, education level, occupation, previous pregnancy experience, socioeconomic status, and access to health information. Insufficient knowledge of these signs, often due to limited access to health services and information, increases the risk of delays in managing pregnancy complications, which can negatively impact both maternal and fetal health. The purpose of this study was to explore the relationship between maternal characteristics, specifically age, and awareness of pregnancy danger signs. This quantitative study employed a correlational approach, using a questionnaire as the data collection tool. The study was conducted at the Tapa Health Center in Bone Bolango Regency, from April to August 2024, with 40 participants included. The Spearman statistical test was used to assess the relationship between maternal characteristics based on age and the knowledge of pregnancy danger signs before and after an intervention. The results showed a significant change in the knowledge levels of pregnant women, with the p-value of 0.852 indicating no direct relationship between maternal age and awareness of pregnancy danger signs. Although a positive change was observed in the knowledge levels after the intervention, the study concluded that there was no significant relationship between maternal age and knowledge of pregnancy danger signs. The findings suggest that while interventions can improve awareness, age alone does not appear to be a significant factor influencing knowledge levels. This highlights the importance of focusing on other factors such as education, health access, and targeted health interventions to enhance maternal awareness of pregnancy risks. Further studies with larger sample sizes and additional variables are recommended to provide a more comprehensive understanding of the factors that influence pregnancy-related knowledge.